Local Wisdom of the Rantau Panjang Community, Simpang Hilir District, Kayong Utara Regency in Utilizing Medicinal Plants - Muhammad Saupi; Hikma Yanti; Yeni Mariani; Fathul Yusro (Jurnal Biologi Tropis, 2021)
Medicinal plants for modern society today are still one of the alternative options in healthcare treatment. This condition is due to the local culture, tradition, and wisdom of a group of people that are still solid and thick. This study aims to analyze the types of medicinal plants used by the community in Rantau Panjang, Simpang Hilir District, North Kayong Regency. This research uses the survey method by conducting interviews with the community and identifying medicinal plants in the field. A sampling of the people who became respondents was done with a purposive sampling technique. The total number of respondents is 333 people distributed in several sub-village, namely Sepakat Jaya 71 people, Tembok Baru 65 people, Ampera 37 people, Makmur 61 people, Sinar Palung 25 people, Kebal Manuk 12 people, Sinar Selatan 35 people and Siput Lestari 27 people. The data obtained were analyzed for Use Value (UV) and Fidelity Level (FL). The village community of Rantau Panjang utilizes 69 types of medicinal plants, with the predominant plant family is Zingiberaceae. The highest use of plant parts is leaves (37.68%), the most common method of processing is boiled (57.97%), and the most extensive way of use is drunk as much as (60.86%). The plants with the highest UV values are turmeric (Curcuma longa L) (0.42), red liyak (Zingiber officinale Linn) (0.34), white turmeric (Curcuma zedoaria L) (0.28), and betel (Piper betle L) (0.22). The types of plants have the highest FL value (100), namely simpur, ketumbar, sawo, leban, pulai, jantung pisang, bunga raya, alalang, durian, nipah, kopi, selo daging, keladi, paku ikan, pegage, kumis kucing, mahkota dewa, belange, belimbing pelunjuk, asam jawa, andong, limau sambal, jambu biji, lidah buaya, pinang, leban, mentimun, daun salam, mentimun, manggis, bajakah, cempedak, pandan wangi, pasak bumi, tebu merah, jengkol, cengkodok, anggrek dan ketepeng.